Essential Oil Composition of Roots of Heracleum candicans Wall. Cultivated in Nursery. Issue 4 (4th July 2018) - Chauhan, Rajendra S.; Nautiyal, M.C.; Rawat, Sanskrita; Tava, A.; Cecotti, R.
Abstract: Heracleum candicans Wall. (Apiaceae) is one of the important endangered aromatic species within the genus Heracleum . Owing to multiple uses, high market demand and endangered status of species, a wild strain was domesticated at Pothivasa (2200 m asl). Roots were dug out during senescence stage in November and essential oil was extracted. Twenty constituents composed of 93.52 % of the total volatile part could identify by using GC-FID and GC-MS analysis. The major portion of the volatile was α-and β-pinene. The study reveals interesting information about the H. candicans that major component of the essential oil varied between underground and leaf parts. Other important constituents were myrcene, germacrene D, dill apiole, limonene, Z-β-ocimene, cyclosativene, sabinene. The characterization of volatile part from cultivated roots opens new avenues for research on medicinal, aromatic and industrial use of H. candicans .